Cykelsport og fremskridtsoptimisme - Møller, Verner (Forum for Idræt, 2001)
Tese: Doping i cykelsporten hænger sammen med sportens genuint moderne karakter. Competitive cycling and confidence in progress This article is a reflection on the fact that studies have demonstrated that doping is more common in competitive cycle racing than in other branches of sport. It attempts to show that this is a difference that is historically determined. The thesis that forms the background for this analysis is that the use of doping in competitive cycling is related to its genuinely modern nature. The author argues that the use of doping mirrors modernity’s confidence in progress and goes on to show that in all probability the crisis in competitive cycling is no chance consequence of police raids in France and Italy, but must be understood fundamentally as a consequence of the crisis of modernity. While competitive cycling in practice mirrors modernity’s confidence in progress by unconcernedly making use of performance enhancing substances produced by modern science, the relatively new anti-doping campaign is an expression of increasing concern and uncertainty regarding the project called modernity. In other words the miserable state of competitive cycling mirrors the fact that modernity has gone out of fashion and anti-modernity is now “in”.